Cytological-energy analysis of pleural effusions with predominance of neutrophils - Matuchova, Inka; Kelbich, Petr; Kubalik, Jan; Hanuljakova, Eva; Stanek, Ivan; Maly, Vilem; Karpjuk, Ondrej; Krejsek, Jan (Therapeutic advances in respiratory disease, 2020)
BACKGROUND: The predominance of neutrophils in pleural effusions of patients with different serious impairments of the pleural cavity organs is often found. The aim of this study was to identify the type of injury using the cytological-energy analysis of pleural effusions. METHODS: We analysed 635 samples of pleural effusions with predominance of neutrophils. We compared the values of the coefficient of energy balance (KEB), lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) catalytic activities in the following subgroups of patients: with transudative effusions, purulent pneumonia, chest empyema and after chest surgery with and without purulent complications. Statistical analysis was performed using the ANOVA Kruskal-Wallis test (p < 0.05 was considered as significant). RESULTS: We found the lowest KEB values in pleural effusions of patients with chest empyema and their gradual increases in patients with purulent pneumonia and with transudative effusions. We observed the highest LDH and AST enzymes activity in patients with chest empyema and their gradual decrease in patients with purulent pneumonia and with transudative effusions. LDH and AST enzymes activity was significantly higher in pleural effusions of patients after chest surgery with purulent complications compared with non-purulent cases. CONCLUSION: The most intensive inflammation and the most extensive tissue destruction in the pleural cavity were found in patients with chest empyema. Significantly better parameters were observed in patients with purulent pneumonia. The absence of serious inflammation and the absence of tissue destruction were typical for patients with transudative effusions. Finally, our results confirmed an anticipated higher tissue destruction in patients after chest surgery. Significantly worse injury was found in surgical patients with purulent complications compared with non-purulent ones. The reviews of this paper are available via the supplemental material section.
Keywords: Retrospective Studies; L-Lactate Dehydrogenase; retrospektivní studie; empyém pleurální; Humans; energetický metabolismus; Aspartate Aminotransferases; pooperační komplikace; lidé; aspartátaminotransferasy; Postoperative Complications; Energy Metabolism; neutrofily; hrudní chirurgické výkony; Pneumonia; Biomarkers; biologické markery; Pleural Effusion; Thoracic Surgical Procedures; Neutrophils; L-laktátdehydrogenasa; pneumonie; pleurální výpotek; Empyema, Pleural